Development and Validation of Instruments for Lifelong Learning Evaluation in the Context of Community Learning Centers - Siswanto, Yudi (Lifelong Education Journal, 2025)
This research aims to develop and validate authentic evaluation instruments for lifelong learning in the context of Community Learning Center (CLC). Quantitative methods with a survey approach were used on 120 CLC tutors as respondents. The analysis stages include exploratory factor analysis to explore factor structure and confirmatory factor analysis to test the validity of constructs. The test results confirmed the existence of four main dimensions: learning motivation, critical thinking, information literacy, and adaptability and independent learning, which consisted of 19 items measured with high-factor load items. The instrument showed strong internal reliability with adequate Cronbach's alpha values and construct reliability, as well as convergent validity through average variance extracted. Respondents' profiles reflect a representative demographic diversity. This instrument is relevant for use in the evaluation of CLC programs and the development of non-formal education curricula, supporting the strengthening of a culture of lifelong learning. This research makes a theoretical and practical contribution in measuring and developing the capacity of lifelong learners in non-formal institutions. The next research suggestion is to expand validation with a more diverse population to improve the generalization of results.